Government Servants conduct & Disciplinary Laws - Muhammad Abdul Basit; Muhammad Abdul Basit (Lahaore New Fine Press Lahore, 2017)
Duties of Public Functionaries an Introduction 2 The government Servants (efficiency and Discipline )Rules, 1973 -3 The Civil Servants Appeal Rules, 1977 4 The government Servants Conduct Rules, 1964 5 The government Servants marriage with Foreign nationals Rules, 1962
Duties of Public Functionaries an Introduction 2 The government Servants (efficiency and Discipline )Rules, 1973 -3 The Civil Servants Appeal Rules, 1977 4 The government Servants Conduct Rules, 1964 5 The government Servants marriage with Foreign nationals Rules, 1962
Keywords: Duties of Public Functionaries an Introduction 2 The government Servants (efficiency and Discipline )Rules, 1973 -3 The Civil Servants Appeal Rules, 1977 4 The government Servants Conduct Rules, 1964 5 The government Servants marriage with Foreign nationals Rules, 1962